Women's career priority is associated with attitudes towards family planning and ethical acceptance of reproductive technologies. Issue 10 (30th August 2017) - Simoni, Michael K.; Mu, Lin; Collins, Stephen C.
ABSTRACT: STUDY QUESTION: Do women who place high importance on career success have different perceptions of pregnancy planning, delayed reproduction, and the ethical acceptability of ART than women with less emphasis on their career? SUMMARY ANSWER: Career-focused women place more importance on pregnancy planning, have greater confidence in delayed childbearing, and are more ethically accepting of donor gamete ART than women who do not place as much importance on career success. WHAT IS KNOWN ALREADY: Women in high-professional careers are more likely to delay childbearing while simultaneously possessing a stronger desire for motherhood. The underlying values which enable these competing desires have not been elucidated. STUDY DESIGN, SIZE, DURATION: This cross-sectional study utilized data from the National Survey of Fertility Barriers (NSFB), a nationally representative telephone survey of US women aged 25–45. Funded by the Eunice Kennedy Shriver National Institute of Child Health and Human Development, the NSFB surveyed 4712 women from 2004 to 2007. PARTICIPANTS/MATERIALS, SETTING, METHODS: In addition to demographic data, the NSFB obtained information about the reproductive history and personal values of participants. Weighted multivariate regression analysis was used to assess reproductive values in career-focused women. MAIN RESULTS AND THE ROLE OF CHANCE: In total, 48.8% of women considered success in work very important, while 17.3% considered it somewhat or not important. Women who placed less value on career success were less likely to consider pregnancy planning important and were less optimistic about the success of delayed childbearing than their work-centric counterparts. Women less focused on their careers were also more likely to have serious ethical concerns about donor gametes, but less likely to have ethical concerns about IUI or IVF, when compared to career-focused women. LIMITATIONS, REASONS FOR CAUTION: Intention to bear children could not be evaluated in the setting of career intentions due to a lack of data on when the participant intended on pursuing motherhood. Political preferences on reproductive health were also not evaluated. The validity of the career priority questions has not been assessed. Additionally, respondents' value statements were not matched to subsequent actions, so it remains possible that these values do not directly impact reproductive behaviors. WIDER IMPLICATIONS OF THE FINDINGS: Our results suggest that reproductive counseling for career-focused women should focus on effective contraception when attempting to delay pregnancy, improved knowledge about age-related fertility decline, and the scope and limitations of current reproductive technologies. In addition, the unique reproductive views of career-focused women suggest that they may benefit from increased employer/insurer support for strategies to enable delayed childbearing, such as fertility preservation and third-party reproduction. STUDY FUNDING/COMPETING INTEREST(S): None.